ANALISIS PROBLEMATIKA PEMBELAJARAN DARING SISWA KELAS VIII PADA MATERI BARIS DAN DERET DITINJAU DARI PEMAHAMAN KONSEP - Nisrina Aliyyunnisa (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2020)
Abstract Online learning is a learning system that is not conducted face-to-face directly, but uses a platform that simplifies the teaching and learning process so that it can be carried out over long distances. However, there are many problems with online learning. SMP Muhammadiyah Plus Gunungpring was selected as the research topic because, from the data obtained, the average score of SMP Muhammadiyah Plus Gunungpring students in math, especially in relation to line and serial material, is still moderate. The method used in this study is qualitatively descriptive. The data in this study is test result data and student response data related to the problem of understanding concepts in line and serial material. In practice, due to the ongoing Covid-19 pandemic, the research was done online using Google Form. The results of this study showed that when students were unable to solve the line and series problems mathematically, students' understanding of the concepts of line and series material was rather moderate. This is because when studying online, students experience issues with unstable connections, lack of parenting support, and boredom from monotonous exposure to material..